2003
DOI: 10.1063/1.1586271
|View full text |Cite
|
Sign up to set email alerts
|

An explicit filtering method for large eddy simulation of compressible flows

Abstract: A method for large eddy simulation (LES) is presented in which the sub-grid-scale modeling is achieved by filtering procedures alone. The procedure derives from a deconvolution model, and provides a mathematically consistent approximation of unresolved terms arising from any type of nonlinearity. The formal steps of primary filtering to obtain LES equations, approximate deconvolution to construct the subgrid model term and regularization are combined into an equivalent filter. This filter should be an almost p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
139
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 341 publications
(140 citation statements)
references
References 19 publications
1
139
0
Order By: Relevance
“…The selective filtering is applied explicitly every second iteration to remove the grid-to-grid oscillations without affecting the resolved scales, but also to provide the effects of the subgrid energydissipating scales. The LES approach based on explicit filtering has been successfully used by different authors for various flows [8,11,12,13]. It has been shown in particular that the filtering does not artificially decrease the effective flow Reynolds number unlike subgrid models based on eddy-viscosity [9].…”
Section: Simulation Parametersmentioning
confidence: 99%
“…The selective filtering is applied explicitly every second iteration to remove the grid-to-grid oscillations without affecting the resolved scales, but also to provide the effects of the subgrid energydissipating scales. The LES approach based on explicit filtering has been successfully used by different authors for various flows [8,11,12,13]. It has been shown in particular that the filtering does not artificially decrease the effective flow Reynolds number unlike subgrid models based on eddy-viscosity [9].…”
Section: Simulation Parametersmentioning
confidence: 99%
“…Low order filters can also obtain good results. It is similar to the strategy used by Mathew et al (Mathew et al 2003). A one-dimensional filter given by Vasilyev et al (Vasilyev et al 1998) is defined as:…”
Section: Discrete Filtersmentioning
confidence: 99%
“…Mathew et al [27] have shown that filtering provides a mathematically consistent approximation of unresolved terms arising from any type of nonlinearity. Filtering regularizes the solution, and generates virtual subgrid model terms that are equivalent to those of approximate deconvolution.…”
Section: The Les Approachmentioning
confidence: 99%
“…Equation (27) illustrates that Fourier components of the filtered function φ m are related to those of the original function by…”
Section: The Compact Filtering Schemementioning
confidence: 99%